2021
DOI: 10.1590/fst.17020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of roasted and unroasted terebinth (Pistacia terebinthus) on the functional, chemical and textural properties of wire-cut cookies

Abstract: The study aimed to access the effects of roasted and unroasted terebinth (0, 10, 20, 30, 40, and 50%) added to cookies to improve their physical, chemical, functional, and textural characteristics. The addition of terebinth to the cookie formulation significantly increased the ash, protein, fat, total dietary fiber, total phenolic matter, and antioxidant content and decreased the phytic acid content of the cookie samples. With the addition of roasted and unroasted terebinth, it was determined that L*, b* value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
4
0
5
Order By: Relevance
“…Different formulations in cookies have been tested by adding various non-conventional food materials such as fruit bagasse, terebinth, green grain flour legume, among others, showing an increase in biological potential and improvement of sensory quality (Köten, 2021;Tarasevičienė et al, 2021;Maia et al, 2021).…”
Section: Consumer Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Different formulations in cookies have been tested by adding various non-conventional food materials such as fruit bagasse, terebinth, green grain flour legume, among others, showing an increase in biological potential and improvement of sensory quality (Köten, 2021;Tarasevičienė et al, 2021;Maia et al, 2021).…”
Section: Consumer Testmentioning
confidence: 99%
“…Therefore, this study aimed to make cookies using heat-treated quinoa (boiling and microwaving) and determine whether the type of heat treatment modifies the phenolic compounds content, antioxidant activity, and bioaccessibility. Cookies were selected for this study due to their long shelf life, high nutrient density, function as a food carrier of bioactive compounds, and convenience as a functional "ready-to-eat" food (Köten, 2021). used according to the specifications indicated on the product label.…”
Section: Introductionmentioning
confidence: 99%
“…Ekmek üretimleri, açık (düz) ekmek üretimi yapan yerel bir fırında gerçekleştirilmiştir. Fitik asit miktarı Köten (2021)'in bildirdiği metoda göre yapılmıştır. 0.1 gr un inceliğinde öğütülmüş örnek 15 ml'lik falkon tüpüne alınmış ve üzerine 10 ml 0.4 M HCI (Merck 100317) içinde çözündürülmüş %10'luk Na2SO4 (Merck 106649) eklenmiştir.…”
Section: Materyalunclassified
“…The higher protein content in CC-6 is associated with the chichá almond, which is a source of this nutrient. Köten (2021) analyzed cookies supplemented with terebinth, and reported a protein content from 9.67 to 10.53%, indicating that turpentine increased this nutrient. Thus, both the cookies produced by Köten (2021) and those analyzed in this study showed increased protein levels, making them more nutritive.…”
Section: Determination Of Bioactive Compounds and Antioxidant Activitymentioning
confidence: 99%
“…cookie production, by adding high nutritional and functional value to the products (Uthumporn et al, 2015). In addition, cookies are widely consumed due to their convenience and low cost (Köten, 2021).…”
Section: Introductionmentioning
confidence: 99%